Structural fracture scales in shock-loaded epoxy composites; Physical Mesomechanics; Vol. 18, iss. 1 - Stukhlyak P. D. Petr Danilovich; Buketov A. V. Andrey Viktorovich; Panin S. V. Sergey Viktorovich; Marushchak P. O. Pavel Orestovich; Moroz K. M. Konstantin Mikhaylovich; Poltaranin M. A. Mikhail Aleksandrovich; Vukherer T. Tomas; Kornienko L. A. Lyudmila Aleksandrovna; Lyukshin B. A. Boris Aleksandrovich (2016, 2016)
Title screen